Radiation-induced eosinophil increase ratio predicts patient outcomes in non-small celllung cancer - Wang, Nuo-Han; Zhang, Xin; Sui, Jiang-Dong; Wang, Ying; Wu, Yong-Zhong; Lei, Qian-Qian; Tu, Hong-Lei; Yang, Li-Na; Liu, Yun-Chang; Yang, Meng-Qi; Yang, Hao-Nan; Li, Dan; et al. (Frontiers in Oncology, 2022)
Background and Purpose: Radiotherapy (RT) is a double-edged sword in regulating immune responses. This study aimed to investigate the impact of thoracic RT on circulating eosinophils and its association with patient outcomes in non-small cell lung cancer (NSCLC). Materials and Methods: This retrospective study included 240 patients with advanced NSCLC treated with definitive thoracic RT from January 2012 to January 2020. Statistics included Kaplan-Meier analysis of overall survival (OS) and progression-free survival (PFS), multivariate Cox analyses to identify significant variables, and Spearman’s correlation to qualify the relationship between dose-volume histogram (DVH) parameters and EIR. Results: Absolute eosinophil counts (AECs) showed an increasing trend during RT and an obvious peak in the 1st month after RT. Thresholds of eosinophil increase ratio (EIR) at the 1st month after RT for both OS and PFS were 1.43. Patients with high EIR above 1.43 experienced particularly favorable clinical outcomes (five-year OS: 21% versus 10%, P<0.0001; five-year PFS: 10% versus 8%, P=0.014), but may not derive PFS benefit from the addition of chemotherapy to RT. The higher a patient’s EIR, the larger the potential benefit in the absence of chemotherapy. DVH parameters including heart mean dose and heart V10 were negatively associated with EIR. None of these DVH parameters was correlated with the clinical outcomes. Conclusion: EIR may serve as a potential biomarker to predict OS and PFS in NSCLC patients treated with RT. These findings require prospective studies to evaluate the role of such prognostic marker to identify patients at risk to tailor interventions.